New one-step thiol functionalization procedure for Ni by self-assembled monolayers - Fontanesi, Claudio (Langmuir : the ACS journal of surfaces and colloids, 2015)
This article reports on a facile and fast strategy for the self-assembled monolayer (SAM) functionalization of nickel surfaces, employing cyclic voltammetry (CV) cycling of a suitable tailored solution containing the species to be adsorbed. Results are presented for ultrathin films formed on Ni by 1-hexadecanethiol (C16), L-cysteine (L-cys), and the poly{methyl (2R)-3-(2,2'-bithiophen-4-ylsulfanyl)-2-[(tert-butoxycarbonyl)amino]propanoate} (PCT-L) thiophene-based chiral polymer. The effective formation of high-quality ultrathin organic films on the nickel was verified both electrochemically and by exploiting typical surface characterization techniques such as contact angle, ellipsometry, atomic force microscopy (AFM), polarization modulation-infrared reflection-absorption spectroscopy (PM-IRRAS), and X-ray photoelectron spectroscopy (XPS)